LEARNERS’ AGENCY IN FOCUS: INTRODUCING THE 21ST CENTURY ACADEMIC WRITING PEDAGOGY IN INDONESIA - Lala Bumela Sudimantara (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
The notion of transformative learning has been echoed by the Indonesian government in the National Standard of Education (2020, 2015). A shift from the teacher-centric into the student-centric pedagogy is a prerequisite to trigger the learning transformation. However, in the field of English language teaching (ELT) in particular, there remains a firm reliance on the dogma of modern linguistics that positions linguistic description and grammatical mastery as the key for meaning-making mechanism. Consequently, such monolithic ELT pedagogy expects a steady compliance from the students in relation to learning, and thus learners’ creative agency was removed. This paper is a reflection on how the learning of academic writing unit was approached differently by using a multisensorial-multicognitive pedagogy as informed by neuroscience, thus breaking away from linguistics as the sole informing theory for learning language. This new academic writing pedagogy embraces language learning as a complex system, thus incorporating other bio-psychological components in learning such as rhythm, intonation, movement, emotion, and aesthetics. This paper highlights how these components were used creatively in the three innovative learning tools – Verbotonal Approach, Reading for Emotions, and Aesthetics – to support agentive learning practice in academic writing course. This new pedagogy was developed in a doctoral research project in an Australian university and was proven effective to help students transform their learning practices.